2022
DOI: 10.1371/journal.ppat.1010227
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin(ogen) engagement of S. aureus promotes the host antimicrobial response and suppression of microbe dissemination following peritoneal infection

Abstract: The blood-clotting protein fibrin(ogen) plays a critical role in host defense against invading pathogens, particularly against peritoneal infection by the Gram-positive microbe Staphylococcus aureus. Here, we tested the hypothesis that direct binding between fibrin(ogen) and S. aureus is a component of the primary host antimicrobial response mechanism and prevention of secondary microbe dissemination from the peritoneal cavity. To establish a model system, we showed that fibrinogen isolated from FibγΔ5 mice, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
5
9
0
Order By: Relevance
“…Additionally, it is possible to hypothesize that anticoagulants may influence inflammation and immune responses against H. pylori infection by inhibiting the coagulation cascade. Fibrin, an end product of the coagulation cascade, is known to play a protective role during infection by limiting bacterial dissemination and activating the antimicrobial properties of monocytes and macrophages [27,28]. A previous study showed an increased level of fibrin in the gastric mucosa of H. pyloripositive patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is possible to hypothesize that anticoagulants may influence inflammation and immune responses against H. pylori infection by inhibiting the coagulation cascade. Fibrin, an end product of the coagulation cascade, is known to play a protective role during infection by limiting bacterial dissemination and activating the antimicrobial properties of monocytes and macrophages [27,28]. A previous study showed an increased level of fibrin in the gastric mucosa of H. pyloripositive patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus strains that secrete exotoxins and exoenzymes can disrupt endothelial and epithelial barriers via cell lysis and junction protein cleavage (Tam and Torres, 2019). Adhesins allow S. aureus to attach to host cells and the extracellular matrix during the early colonization phase (Negron et al, 2022). Nutritional/metabolic factors are critical for the fitness of S. aureus and its adaptation to nutritionally diverse environments (Balasubramanian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Among these interactions, Fg seems to play a dominant role (8) Also the role of Fg is at the crossroad between its well described role in haemostasis and its importance in mediating immune response (14,48). Much preclinical evidence also showed that mutated versions of Fg cannot efficiently clear infection mediated by S. aureus thus compromising immune response towards the pathogen (19)(20)(21)49). Furthermore, preclinical studies together with vaccine candidates have shown that ClfA-mediated Fg interaction is a viable alternative for possible therapeutic strategies (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recent evidence has demonstrated that the interaction with Fg may drive different host responses based on the tissutal context (8). In peritonitis mouse infection models, binding of Fg is fundamental to elicit an antibacterial response and contain infection (18)(19)(20)(21). However, the picture is completely reversed in bloodstream infections, where Fg instead promotes spreading of S. aureus (22).…”
Section: Introductionmentioning
confidence: 99%